2020
DOI: 10.1128/mra.00568-20
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a Novel Coronavirus (SARS-CoV-2) Isolate from Bangladesh

Abstract: The complete genome sequence of a novel coronavirus (severe acute respiratory syndrome coronavirus 2 [SARS-CoV-2]) isolate obtained from a nasopharyngeal swab from a patient with COVID-19 in Bangladesh is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 11 publications
2
30
0
Order By: Relevance
“…As SARS-CoV-2 genomes spread, they leave footprints behind (mutations) allowing us to trace them. From this footprint, we have found that mutational frequency in the circulating SARS-CoV-2 genome in Bangladesh is fluctuating over time which is supported by another recent study by Saha et al, 2020c . It is feasible to complement the conventional approach with genome sequencing in an unbiased way.…”
Section: Discussionsupporting
confidence: 82%
“…As SARS-CoV-2 genomes spread, they leave footprints behind (mutations) allowing us to trace them. From this footprint, we have found that mutational frequency in the circulating SARS-CoV-2 genome in Bangladesh is fluctuating over time which is supported by another recent study by Saha et al, 2020c . It is feasible to complement the conventional approach with genome sequencing in an unbiased way.…”
Section: Discussionsupporting
confidence: 82%
“…MN908947.3, https://github.com/czbiohub/sc2-msspe-bioinfo ). 15 , 16 Consensus sequences of the 9 SARS-CoV-2 genomes were uploaded on GISAID 17 and subsequently analyzed using NextStrain ( https://nextstrain.org/ ). 18 …”
Section: Methodsmentioning
confidence: 99%
“…(I300F), can be a destabilizing factor for nsp2 and thus modulating the strategy of host cell survival [11,20]. This mutation can lead to a reduction of conformational entropy due to the presence of the side chains that can result in charge neutralization of the phosphorylated serine residues [21].…”
Section: Prevalence Of Global Common Mutationsmentioning
confidence: 99%